A German Travels to the North in 1878: Golden Anitos, Bird-Scaring Machines, and the Tree of Justice - Guillermo, Ramon (Archīum Ateneo, 2013)
After ﬁnishing his education at the University of Munich, the German pharmacist Dr. Heinrich Rothdauscher (1851–1937) spent the years 1873 to 1883 working in drugstores in Manila, Cebu, and Vigan. He eventually ﬁnished writing an account of his experiences in a work entitled “Memoirs of a German Pharmacist” in 1932. Presented here is a translation of two chapters of a short expedition to the Cordilleras in 1878, which contain interesting literary, historical, and ethnographic elements.Keywords: Travel memoirs • German • PhiliPPines • The Cordilleras • ifuGao